Flavonoid-Rich Fraction of Ocimum gratissimum Attenuates Lipopolysaccharide-Induced Sickness Behavior, Inflammatory and Oxidative Stress in Mice - Ajayi, Abayomi M.; Ben-Azu, Benneth; Onasanwo, Samuel A.; Adeoluwa, Olusegun; Eduviere, Anthony; Ademowo, Olusegun G (Drug Research, 2019)
PurposeOcimum gratissimum L. leaves has been traditionally used for management of febrile illnesses and symptoms typified of sickness behavior. In this work we investigated the modulatory effect of flavonoid-rich fraction of O. gratissimum leaves (EAFOg) on sickness behavior, inflammatory and oxidative stress responses in LPS-challenged mice.MethodO. gratissimum leaf was first extracted with n-hexane, chloroform and methanol, and EAFOg was obtained by ethylacetate partitioning of a sequentially resultant methanol extract. The effect of EAFOg (25–100 mg/kg) on acute LPS-induced neurobehavioral impairment in an open field test (OFT) and depressive-like behavior in forced swimming test (FST) was investigated. Serum nitrite and TNF-α, as well as myeloperoxidase (MPO), malondialdehyde (MDA), and reduced glutathione (GSH) levels were determined in liver and brain tissues.Result EAFOg prevented the reduction in locomotor and rearing activity in OFT and the increase in immobility time in FST. The fraction significantly attenuated the elevation of serum TNF- α and nitrite levels. EAFOg reversed LPS-induced increase in MDA, MPO, and nitrite levels and attenuated GSH depletion in liver and brain tissues of mice.Conclusion Flavonoid-rich fraction of O. gratissimum leaf demonstrated significant modulation of LPS-induced sickness behavior, inflammatory and oxidative stress response in mice. This suggests an important therapeutic strategy in slowing down LPS-mediated hepatic and neuronal disease processes.
Keywords: Ocimum; sickness behaviour; lipopolysaccharides; flavonoids